2016
DOI: 10.1002/cmmi.1707
|View full text |Cite
|
Sign up to set email alerts
|

Cellular internalization and morphological analysis after intravenous injection of a highly hydrophilic octahedral rhenium cluster complex – a new promising X‐ray contrast agent

Abstract: The octahedral cluster compound Na H [{Re Se }(P(C H CONH )(C H COO) ) ] has been shown to be highly radio dense, thus becoming a promising X-ray contrast agent. It was also shown that this compound had low cytotoxic effect in vitro, low acute toxicity in vivo and was eliminated rapidly from the body through the urinary tract. The present contribution describes a more detailed cellular internalization assay and morphological analysis after intravenous injection of this hexarhenium cluster compound at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Actually,e lectron-rich octahedral clusters exhibit highly appealing optical properties such as phosphorescence in the NIR region triggered by UV,v isible light or even X-ray irradiation [14] with lifetimes up to severalh undred microseconds and exceptionally high quantum yield, making this class of material highly relevantf or bioimaging [15] or biolabelling applications. [16] Additionally,t his class of compounds exhibit high radiodensity due to close packingo fh eavy elements in the cluster core {M 6 Q 8 }w ith M = Mo, Wo rR e; Q= Se, Te ,B ro rIwhich is a pre-requisite for X-ray contrast agents and thereby useful for bimodal bioimaging. [17] Moreover,o ctahedral clusters behave also as potentiala ntitumoral and antimicrobial agents due to their ability to generate singlet oxygen upon photoirradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Actually,e lectron-rich octahedral clusters exhibit highly appealing optical properties such as phosphorescence in the NIR region triggered by UV,v isible light or even X-ray irradiation [14] with lifetimes up to severalh undred microseconds and exceptionally high quantum yield, making this class of material highly relevantf or bioimaging [15] or biolabelling applications. [16] Additionally,t his class of compounds exhibit high radiodensity due to close packingo fh eavy elements in the cluster core {M 6 Q 8 }w ith M = Mo, Wo rR e; Q= Se, Te ,B ro rIwhich is a pre-requisite for X-ray contrast agents and thereby useful for bimodal bioimaging. [17] Moreover,o ctahedral clusters behave also as potentiala ntitumoral and antimicrobial agents due to their ability to generate singlet oxygen upon photoirradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the family of octahedral cluster complexes [{Re 6 Q 8 }L 6 ] and [{Mo 6 X 8 }L 6 ] (where X is Cl, Br or I; Q is S, Se or Te and L are organic or inorganic ligands) and materials based on them have been intensively studied in the last few years in the context of biomedical applications. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] First of all, this is due to the progress made in the develop-ment of phosphorescent octahedral molybdenum cluster complexes, all based on the {Mo 6 I 8 } 4+ cluster core that have particularly high quantum yields [34][35][36][37] and high efficiency in generating singlet oxygen. [38][39][40][41][42][43] Specifically, our recent studies have shown that materials doped using {Mo 6 I 8 } 4+ are highly photoluminescent and have low cellular toxicity in the dark, while by a careful selection of a matrix the cellular internalisation and photoinduced toxicity of the materials can be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes with 24 cluster valence electrons can be highly phosphorescent in the red-NIR area. [29][30][31][32][33][34][35] Because of their high potential in biology for ROS production, as nanoscintillators or contrast agents, [36][37][38] in optoelectronic [39][40][41] or lighting, 42 many efforts have been devoted these last years to counterpart their ceramic-like behaviour and integrate them in host matrices. [43][44][45][46][47][48][49][50][51][52][53][54] Hence, several strategies have been developed to solubilize the [M 6 Q i 8 X a 6 ] nanionic units in organic media, 55,56 or to integrate them directly in a polymeric or liquid crystalline organic host matrix 23,25,49,57,58 by replacing, via a metathesis reaction, their alkali counter cations by functional organic ones.…”
Section: Introductionmentioning
confidence: 99%